Mediating Role of Attitude towards Betrayal and Marital Conflict in Relation between Using Virtual Social Networks and Emotional Divorce - Seyedeh Sara Shakeri; jafar Shabani; Hamidreza Aghamohammadian Sharbaf; Seyed Mojtaba Aghili (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: Research results show that unmanaged use of virtual networks is the cause of differences between couples. Accordingly, the present study aimed to determine the mediating role of attitudes toward betrayal and marital conflicts in the relationship between the use of virtual social networks and emotional divorce in married teachers in Mashhad. Methods: The research method was descriptive-correlational and the society included married teachers in seven areas of education in Mashhad city in the academic year of 2017-2018. 375 teachers were selected by quota sampling method and completed questionnaires on social networks, emotional divorce, attitudes toward betrayal and marital conflicts. Data were analyzed using path analysis using Maximum Field Definition (ML). The structural equation modeling was used to analyze data using AMOS software version 25. Results: Based on the findings, the mediating role of attitude toward betrayal was not significant for predicting emotional divorce based on the use of virtual social networks (β = 0.06).The role of conflicting intermediaries is significant for predicting emotional divorce based on the use of virtual social networks. Accordingly, the role of the mediating meanings of marital conflicts along with the non-perceptible role of attitudes toward betrayal, based on the use of virtual social networks, predicts a total of 20% of the variance of emotional divorce. If the direct role of using virtual social networks in predicting emotional divorce along with the role of intermediate variables is considered, 66% of the variance of emotional divorce is predictable. Fit indicators showed the optimal fitness of the model with the collected data. (P <0.05) Conclusion: The results of this study showed that increasing the use of virtual networks with increasing conflicts increases the incidence of emotional divorce in couples.